2015
DOI: 10.1371/journal.pone.0128531
|View full text |Cite
|
Sign up to set email alerts
|

Different Timing Features in Brain Processing of Core and Moral Disgust Pictures: An Event-Related Potentials Study

Abstract: Disgust, an emotion motivating withdrawal from offensive stimuli, protects us from the risk of biological pathogens and sociomoral violations. Homogeneity of its two types, namely, core and moral disgust has been under intensive debate. To examine the dynamic relationship between them, we recorded event-related potentials (ERPs) for core disgust, moral disgust and neutral pictures while participants performed a modified oddball task. ERP analysis revealed that N1 and P2 amplitudes were largest for the core dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 78 publications
3
20
0
Order By: Relevance
“…However, in a lexical decision task, Luo and colleagues demonstrated that core disgust words are distinguished from neutral words in the early EPN component whereas the features of moral words are accessible in subsequent N320 and N400 components 11 . Similar results have been obtained in two recent ERP studies, demonstrating an early disgust effect when processing pictorial stimuli with moral, disgust or neutral content 12 , 13 .…”
Section: Introductionsupporting
confidence: 89%
“…However, in a lexical decision task, Luo and colleagues demonstrated that core disgust words are distinguished from neutral words in the early EPN component whereas the features of moral words are accessible in subsequent N320 and N400 components 11 . Similar results have been obtained in two recent ERP studies, demonstrating an early disgust effect when processing pictorial stimuli with moral, disgust or neutral content 12 , 13 .…”
Section: Introductionsupporting
confidence: 89%
“…Significant differences have been reported at this site, 74 nonsignificant differences have been reported at this site 75 and it has also been suggested that the Pz electrode site is not of importance for this comparison. 70,76,77 In this study, a significant main effect of time at the P4 electrode site was recorded with the P300 amplitudes being large for both violent and neutral images after playing the VVG. It has been demonstrated that the right hemisphere of the brain is superior in processing images, 78 the hemisphere for the P4 electrode.…”
Section: Figmentioning
confidence: 55%
“…Therefore, in this study we analyzed the latencies and amplitudes of the occipital N1 and the frontal P3 across different sets of electrodes in accordance with the relevant literatures (Carlson & Reinke, 2010;Luck, 2005;Liu et al, 2015;D. Zhang et al, 2013;X. Zhang, Guo, Zhang, Lou, & Ding, 2015).…”
Section: Routine Analysis Of Erp Datamentioning
confidence: 99%